Health Education for Enhancement of Self Efficacy of Young Females (Medical Forum Monthly, 2024)
Objective: This study aimed to examine the impact of health education on health related self efficacy of young females as well as the relationship between self efficacy and one’s health knowledge.Study Design: Cross sectional studyPlace and duration of study: This study was conducted at Gender & Development Study Department, Lahore College for Women University, Lahore and was completed over a span of two weeks.Materials and Methods: A purposive sample of 50 young females was exposed to breast cancer related information. Their self efficacy was measured before and after being health educated. The information gathered before and after health information provision was compared. Two instruments were used for gathering information; a) Breast cancer related self-efficacy scale developed by this author which includes three items pertaining to the perceived self-efficacy of the respondents regarding breast cancer, and b) Preaction BSE Self-efficacy scale by Luszczynska and Schwarzer for assessing perceived self-efficacy of the respondents regarding the confidence in performing BSE/ breast self examination in spite of hurdles.1Results: Data analysis revealed that breast cancer related self efficacy was significantly enhanced after health education provision. Young women who seemed to be clueless about a proactive approach to identification and treatment of breast cancer, exhibited significantly higher self efficacy after receiving proper health education.Conclusion: Considering the risk of many life threatening diseases in women there is a need to improve their health behaviors by nurturing self efficacy. Provision of health education at educational institutions and through media can be an effective strategy for attaining this goal.